The Fermi bubbles inflated by winds from the accretion flow in Sgr A*. Issue Volume 10:Issue S312(2014) (7th March 2016) - Mou, Guobin
Abstract: By performing three-dimensional hydrodynamical simulations, we show that the Fermi bubbles could be inflated by winds launched from the "past" hot accretion flow in Sgr A*. The parameters of the accretion flow required in the model are consistent with those obtained independently from other observational constraints. The wind parameters are taken from small scale MHD numerical simulations of hot accretion flows.